2021
DOI: 10.3389/fpsyg.2021.621990
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Personality and Intelligence Toward Cognitive Competences in Higher Education

Abstract: Personality and cognition are found to be two interrelated concepts and to both have a predictive power on educational and life outcomes. With this study we aimed at evaluating the extent to which personality traits interact with cognition in acquiring cognitive competences during higher education. In a sample of university students at different stages of their career and from different fields of study, we collected Big Five traits, as a measure of personality, and Intelligent Quotient (IQ), as a proxy of cogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 76 publications
(118 reference statements)
1
11
0
Order By: Relevance
“…There is evidence supporting the predictive role of personality in accounting for individual differences in performance on large-scale competence assessment tests (Borghans et al, 2016;Cerni et al, 2021). Neuroticism, in particular, was found to negatively correlate with performance on various cognitive tasks.…”
Section: Neuroticism Numeracy and Gender Gap A Possible Connection?mentioning
confidence: 83%
See 3 more Smart Citations
“…There is evidence supporting the predictive role of personality in accounting for individual differences in performance on large-scale competence assessment tests (Borghans et al, 2016;Cerni et al, 2021). Neuroticism, in particular, was found to negatively correlate with performance on various cognitive tasks.…”
Section: Neuroticism Numeracy and Gender Gap A Possible Connection?mentioning
confidence: 83%
“…Neuroticism, in particular, was found to negatively correlate with performance on various cognitive tasks. Higher levels of neuroticism correlated with lower scores on verbal reasoning (Chamorro-Premuzic et al, 2006;Cerni et al, 2021) and intelligence (Moutafi et al, 2006;Graham and Lachman, 2014), as well as with slower reaction times in response inhibition (Graham and Lachman, 2012). Considering numeracy, neuroticism seems to negatively affect numeracy test performance (Spinath et al, 2010;Rammstedt et al, 2016;Brandt et al, 2020), even if findings are not consistent; indeed, in some studies, no association between numerical skills and neuroticism was documented (Chamorro-Premuzic et al, 2006;Meyer et al, 2019;Cerni et al, 2021).…”
Section: Neuroticism Numeracy and Gender Gap A Possible Connection?mentioning
confidence: 98%
See 2 more Smart Citations
“…Most factors of personality characteristics and cognitive ability are very weakly correlated, so the two can be independently used as explanatory variables of individual behavior ( Ackerman and Heggestad, 1997 ); even though some scholars believe that cognitive ability and personality characteristics will affect each other ( Borghans et al, 2008 ). Tania’s research on personality traits has a significant impact on information processing ability (IPA) and found that different personality traits, especially conscientiousness, will reduce the impact on performance according to the increase in education level, indicating that personal personality has a greater impact on the promotion of academic achievement ( Cerni et al, 2021 ). In recent years, the causal relationship between the two has been paid more attention.…”
Section: Introductionmentioning
confidence: 99%